PELATIHAN PENULISAN ARTIKEL JURNAL ILMIAH BAGI SISWA SMA UNGGULAN AL AZHAR MEDAN SEBAGAI UPAYA MENINGKATKAN LITERASI AKADEMIK - Matondang, Khoiruddin; Saragih, Risna Mira Bella; Lubis, Ulfa Annisa; Putri, Jihan Hidayah; Simamora, Minta Ito; Nurhayati, Nurhayati; harahap, Yenni novita; Lubis, Atipah (Fakultas Keguruan dan Ilmu Pendidikan UNIVA Medan, 2025)
Training and assistance in writing scientific journal articles for students of Al Azhar Medan Superior High School is carried out as an effort to improve students' academic literacy. This activity is based on the low ability of students to write scientific papers systematically, even though they have high academic potential. The method of implementing activities was carried out through face-to-face training for three days and online/offline assistance for two weeks. The activity was attended by 25 students of grade XI, and was evaluated using pre-test, post-test, observation, and assessment of writing results. The results of the activity showed an increase in the average score from 58.2 to 82.4, the number of students who were able to compile complete articles increased from 4 to 20 people, and eight articles were declared worthy of publication. In addition, 92% of students stated that this activity was very beneficial. This activity shows that participatory training approaches and systematic mentoring are effective in improving students' scientific literacy. The program also contributes to the formation of an academic culture and sustainable scientific writing skills at the high school level.